2019
DOI: 10.1016/j.renene.2019.02.140
|View full text |Cite
|
Sign up to set email alerts
|

Business and socioeconomic assessment of introducing heat pumps with heat storage in small-scale district heating systems

Abstract: Fossil fuel-based CHP plants have a long history of supplying district heating (DH) in Denmark, however small-scale systems are progressively switching to biomass boilers for economic reasons. Biomass, however, should be reserved for other purposes where a storable fuel is pertinent. This paper investigates the transition of DH on the Danish renewable energy island Samsø. While already renewable energy-based through the use biomass, the system is neither socioeconomically optimal nor optimal in terms of integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 46 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…4) is the Ballen marina located in Samsø (Denmark), where a smart energy system is being installed and tested in the framework of the Horizon2020 European research project SMILE [54]. Samsø was appointed in 1997 as Denmark's renewable energy island and has been the site for many energy innovations which are leading the island to be fossil fuel free by 2030 [56]- [58]. Today, the annual energy demand balances the annual supply from RES (sometimes the island produces more electricity than it consumes owing to offshore and onshore wind power, and a district heating based on biomass) but the island is currently not self-sufficient, yet.…”
Section: Parameters and Settingsmentioning
confidence: 99%
“…4) is the Ballen marina located in Samsø (Denmark), where a smart energy system is being installed and tested in the framework of the Horizon2020 European research project SMILE [54]. Samsø was appointed in 1997 as Denmark's renewable energy island and has been the site for many energy innovations which are leading the island to be fossil fuel free by 2030 [56]- [58]. Today, the annual energy demand balances the annual supply from RES (sometimes the island produces more electricity than it consumes owing to offshore and onshore wind power, and a district heating based on biomass) but the island is currently not self-sufficient, yet.…”
Section: Parameters and Settingsmentioning
confidence: 99%
“…Other tools, such as EnergyPlan, Homer, or RETScreen, are representative of one node models [30] and cannot be used for complex systems, similar studies and/or cannot provide similar results with this level of detail as they have many limitations in network representation, Energy Management Systems (EMS) control customization, and solver capabilities [23], [31]. Similar works in Samsø and Orkney have been performed using EnergyPlan [1], [32], but due to certain capabilities of this software, they refer to a conceptual-design level of detail. The present work intends to provide a higher level of detail, while being in position to calculate key power related variables (not only electricity, but also heating/cooling ones).…”
Section: Methodological Conceptmentioning
confidence: 99%
“…One study showed that the technical and private economic aspects of integrating a large capacity of electric driven heat pumps in the Greater Copenhagen district heating system, which is an example of a state-of-the-art large district heating system with many consumers and suppliers [93]. Heat pump combined with heat storage utilizing wind power locally was also demonstrated in [94] . It is also showed excess heat from industrial thermal processes within 5 km by 5 km Danish Square Grid in Denmark [95].…”
Section: Integration With Other Energy Technologiesmentioning
confidence: 99%